Enterprise risk management disclosure and CEO characteristics: an empirical study of go public companies in Indonesia - Trisnawati, Rina; Mustikawati, Susilaningdyah; Sasongko, Noer (Business: Theory and Practice, 2023)
Organizations can use enterprise risk management disclosures to share financial and non-financial risk information with external stakeholders. Chief Executive Officer (CEO) has a key role in enterprise risk management. This study examines the relationship between Indonesian CEOs’ characteristics and enterprise risk management disclosure. Purposive sampling is the basis for the process of gathering samples from the population. The research was conducted in 2020 and consisted of 475 non-financial Indonesian companies that were listed on the Indonesian Stock Exchange. The findings of previously released annual reports may be found on the websites of both the Indonesia Stock Exchange and individual companies. These secondary sources were used to compile the study data. The ISO framework index 31000:2018 is utilized to evaluate the Enterprise risk management (ERM) disclosure. Eviews10’s implementation of multiple regression serves as the basis for the analysis. The findings indicate that CEO overconfidence and CEO tenure influence enterprise risk management disclosure, while CEO financial expertise and CEO gender did not have an effect on enterprise risk management disclosure. The innovation of this research is investigating CEOs’ characteristics by psychological characteristics, namely CEO overconfidence and measurement of ERM disclosure based on the ISO 31000:2018 framework which is the latest standard of risk management.